Climate-smart agriculture technologies in Nepal: Adoption, policy barriers, and way forward - Pathak, Himanshu (International Food Policy Research Institute, 2025)
This discussion brief is part of the knowledge management and capacity building component of the Consortium for Scaling-up Climate-Smart Agriculture in South Asia (C-SUCSeS) project. CSUCSeS is a joint initiative between the SAARC1 Agriculture Centre (SAC), International Fund for Agriculture Development (IFAD) and International Food Policy Research Institute (IFPRI). It aims to promote bottom-up applied research on climate-smart agriculture (CSA) technologies through active participation of smallholder farmers based on the participatory research experiences in the region.